British Liberalism and the French invasion of Mexico - Middleton, A (Cambridge University Press, 2022)
Napoleon III’s 1860s intervention in Mexico mystified some British observers. For many others, however, it raised urgent questions about the duties of European civilization and the future of global order. This article argues that the affair forced attitudes toward other European countries' overseas imperial projects into sharp political focus, and that in doing so it revealed incipient shifts in the center of gravity of Victorian liberalism. France’s Second Mexican Empire split opinion in the Liberal Party and press, throwing light on wider disputes about the parameters of legitimate imperial intervention, the reach of the principles of nationality and self-determination, the political needs of disordered multiracial polities in less-developed parts of the world, and Europe’s proper relations with Spanish America. But most Liberals who engaged with the enterprise condemned it, a fact that lays bare a changing balance of power between what historians have called “liberal imperial” and noninterventionist arguments in the 1860s. The failure of the intervention, moreover, did much to affirm powerful partisan narratives about French politics, which helped to buttress the electoral ascendency of the Liberal Party.